DOWNLOAD ARTICLE Some aspects of declaring legal acts unconstitutional - Andrii Pomazanov (Юридичний часопис Національної академії внутрішніх справ, 2022)
The relevance of the study is conditioned by a number of problems of declaring legal acts unconstitutional and the specifics of the consequences of such decisions to guarantee the rights of the individual. This requires a review of approaches to the temporal effect of the relevant decisions of the Constitutional Court, to guarantee the right to review court decisions adopted based on an act that has been declared unconstitutional. At the same time, it is necessary to put forward new proposals for legal regulation of the analysed area, optimal for the rule of law and ensuring the right to a fair trial. The purpose of the study is to clarify certain features and consequences of declaring legal acts unconstitutional to further ensure the rights of citizens and make proposals for amendments to the legislation. The methodological basis of the study is the dialectical and materialist method, general and special methods of legal science, in particular, system and structural, comparative law, logical and legal (dogmatic). The scientific originality lies in a comprehensive clarification of the features of the legal consequences of declaring legal acts unconstitutional and making proposals for regulatory settlement of identified problems in the conditions of Ukrainian law enforcement. According to the findings, the importance of guaranteeing the normative and practical connection between the content of the act and its impact on the damage to anyone, the proportionality of ways to compensate, and the range of legal relations in which such damage can be compensated